RNase L facilitates the repair of DNA double‐strand breaks through the nonhomologous end‐joining pathway. Issue 11 (21st May 2019) - Zhong, Yiran; Pan, Bingxin; Zhu, Jie; Fu, Hanjiang; Zheng, Xiaofei
Abstract : RNA molecules have been found to play important roles in DNA double‐strand break (DSB) repair, but the exact underlying mechanism remains unclear. Here, we aimed to clarify the function of RNase L, an important ribonuclease in the immune system of vertebrates, in DSB repair. Knockdown of RNase L reduces cell survival after induction of DSBs by ionizing radiation or camptothecin and causes a significant decrease in DSB repair, as evidenced by an increase in the extent of phosphorylation of histone H2AX on Ser139 (γH2AX) and γH2AX nuclear foci formation. Thus, our findings indicate that RNase L interacts with the core factors involved in DNA end joining, such as XRCC4 and Lig4, and facilitates DSB repair through the nonhomologous end‐joining pathway. Abstract :